Expression of genes involved in drug metabolism differs between perfusable 3D liver tissue and conventional 2D‐cultured hepatocellular carcinoma cells - Mori, Nobuhito (FEBS Open Bio, 2020)
Tubular 3D liver tissue with enhanced capillary‐like structures branching from a large main channel is potentially useful for drug discovery because the perfusable main channel and capillary‐like structures enable mass transfer into and out from the tissue. Tubular liver tissue is comprised of the hepatocellular carcinoma cell line HepG2, human umbilical vein endothelial cells (HUVECs), and mesenchymal stem cells (MSCs), using a perfusion device functioning as the interface for an external pump. This study aimed to compare the expression of genes involved in drug metabolism between 2D‐cultured hepatocellular carcinoma cells and 3D‐cultured tubular liver tissue. Gene expression profiles of 2D‐cultured cells and tubular liver tissue were compared using RNA sequencing. Multidimensional scaling analysis revealed that culture dimensionality had a more prominent effect on gene expression profiles than perfusion conditions. More specifically, genes involved in drug metabolism such as CYP2D6, CYP2E1, NNMT, and SLC28A1 were slightly upregulated in the 3D cultures, while certain genes such as ALDH1B1, ALDH1A2, and SULT1E1 were downregulated. These results indicate that gene expression profiles are largely influenced by culture dimensionality and are potentially useful to researchers intending to switch from 2D culture to 3D culture of hepatocellular carcinoma or other tissue types.